Nutritional status, body composition and diet quality in children with cancer - Schab, Magdalena; Skoczen, Szymon (Frontiers in Oncology, 2024)
During cancer treatment, nutritional status disorders such as malnutrition or obesity affect the tolerance of cancer treatment, quality of life, but also the pharmacokinetics of drugs. It is hypothesized that changes in fat and lean body mass can modify chemotherapy volume distribution, metabolism and clearance. In children with cancer, lean body mass decreases or remains low during treatment and fat mass increases. Body composition is influenced by the cancer itself, aggressive multimodal-therapies, changes in metabolism, unbalanced diet and reduced physical activity. Due to the side effects of treatment, including changes in the sense of taste and smell, nausea, vomiting, diarrhea, and stress, eating according to recommendation for macronutrients and micronutrients is difficult. Research indicates that throughout cancer treatment, the consumption of fruits, vegetables, and dairy products tends to be insufficient, whereas there is an elevated intake of sugar and unhealthy snacks. Children exhibit a preference for high-carbohydrate, salty, and strongly flavored products. This review revealed the importance of body composition and its changes during cancer treatment in children, as well as eating habits and diet quality.